Human Trafficking and Child Education in Nigeria (London Journal of Research In Humanities and Social Sciences, 2024)
This study examines human trafficking and its impact on child education. Human trafficking has had various effects on child education. On this note, the major aim of this work was to explore the relationship between human trafficking and child education, the causes of human trafficking, the effects of human trafficking on child education and ways the government can curb human trafficking and improve child education thereby providing suitable solutions to the problem at hand. The theory used for this project work is conflict theory, conflict theory explains how the dominant classes maintain their power over lower income and ethnic minority groups. The research method used for this study is the qualitative method. An in-depth interview was conducted, and the opinions of the respondents were well articulated and transcribed. Three respondents participated. The result revealed that the causes of human trafficking are poverty, lack of education, ineffective law/unenforced law, unemployment, and ignorance. Also, the research showed that there is a relationship between human trafficking and child education in Lagos State. The government should make laws stronger, work together with other countries to stop trafficking, campaigns should be created in order to teach people about the dangers of human trafficking in order to curb human trafficking and promote child education.
Keywords: : Integrated music and art education; Animals in classical music; Art interpretation of animal imagery; Music-art matching; Children Environmental Stressors Vulnerability Women; Nigeria; Violence; children; Child Education; Human Trafficking